Role of Honey in Obesity Management: A Systematic Review - Ugusman, Azizah; Shahrin, Syarifah Amirah Syed; Azizan, Nurul Hana; Pillai, Siva Balan; Krishnan, Khamini; Salamt, Norizam; Aminuddin, Amilia; Hamid, Adila A.; Kumar, Jaya; Mokhtar, Mohd Helmy (Frontiers in Nutrition, 2022)
Obesity is a metabolic disorder that has become critically prevalent throughout the world. Obesity has been linked to other chronic diseases such as diabetes mellitus, cardiovascular diseases and cancer. Natural products such as honey have been investigated for their potential effect on obesity. Hence, this study systematically reviewed the recent literature concerning the effects of honey on obesity in obese animal models and in people with obesity. The Ovid MEDLINE, PubMed, Scopus, Web of Science and Google Scholar electronic databases were searched for relevant articles. A total of 130 relevant articles were obtained from the initial search. Following a thorough screening, nine articles were selected for data extraction, including six animal studies and three clinical trials. In most of the animal studies, honey demonstrated an anti-obesity effect by reducing body weight, body fat composition and adipocyte size, among others. However, supplementation of honey in clinical trials showed conflicting results. Even though honey supplementation did not demonstrate any weight-reducing effect in some of the clinical trials, none of the trials showed that honey increases body weight. However, the results should be interpreted with caution as most of the studies involved animal models and there is a limited number of high quality, randomized, controlled clinical trials.